Cover Feature: Indoles from Alkynes and Aryl Azides: Scope and Theoretical Assessment of Ruthenium Porphyrin‐Catalyzed Reactions (Chem. Eur. J. 72/2019). Issue 72 (29th November 2019) - Intrieri, Daniela; Carminati, Daniela Maria; Zardi, Paolo; Damiano, Caterina; Manca, Gabriele; Gallo, Emma; Mealli, Carlo
Abstract : The targeted combination of experimental and in silico techniques permitted a good understanding of key mechanistic aspects of the one‐pot synthesis of a large class of indoles from alkynes and aryl azides, which was efficiently catalyzed by ruthenium bis‐imido porphyrin complexes. The cover aims to highlight the efficiency of the symbiotic approach, which may help optimizing the sustainable production of valuable fine‐chemicals. More information can be found in the Full Paper by G. Manca, E. Gallo et al. on page 16591 .